Getting the Most Out of Free Trade Agreements in Central America - Lopez, J. Humberto (World Bank, 2012)
Peace came accompanied not only by the end to the human drama associated with the conflicts, but also by a significant economic dividend, a much needed development in a region where per capita gross domestic product (GDP) had stagnated between 1970 and 1990 and where two countries (El Salvador and Nicaragua) had been experiencing negative average growth rates for more than two decades. The social dimension of the dismal growth performance is well captured in the poverty rates. According to World Bank statistics, in the first half of the 1990s the average poverty rate in the region was close to 60 percent in countries such as Honduras and Nicaragua; almost three-quarters of the population lived on less than US$4 a day. Several lessons emerge from getting the most out of free trade agreements (FTAs) in Central America, but the author will like to stress three. First, Central America should not take the positive results of signed FTAs as a given. Second, trade promotion needs to be complemented by a strong focus on the poor. In some cases, this focus is because of the challenges brought by additional external competition, which may negatively affect some industries or sectors. Third, is the need for more competitive markets? Although many of us tend to think about the benefits of growth in terms of quantities (that is, more exports, more employment, and increased access to goods) many of the welfare effects of FTAs are transmitted through prices (such as lower prices for imported goods).